2018
DOI: 10.1038/s41467-018-05711-6
|View full text |Cite
|
Sign up to set email alerts
|

p53 in AgRP neurons is required for protection against diet-induced obesity via JNK1

Abstract: p53 is a well-known tumor suppressor that has emerged as an important player in energy balance. However, its metabolic role in the hypothalamus remains unknown. Herein, we show that mice lacking p53 in agouti-related peptide (AgRP), but not proopiomelanocortin (POMC) or steroidogenic factor-1 (SF1) neurons, are more prone to develop diet-induced obesity and show reduced brown adipose tissue (BAT) thermogenic activity. AgRP-specific ablation of p53 resulted in increased hypothalamic c-Jun N-terminal kinase (JNK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 81 publications
1
50
0
1
Order By: Relevance
“…7,8,35 Considering that the increase in body weight following hepatocyte-specific p53 ablation was independent of food intake and associated with a decrease in energy expenditure, the mechanism of action underlying this impairment likely relates to p53's role in mitochondrial energetics. 7,8,35 Considering that the increase in body weight following hepatocyte-specific p53 ablation was independent of food intake and associated with a decrease in energy expenditure, the mechanism of action underlying this impairment likely relates to p53's role in mitochondrial energetics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…7,8,35 Considering that the increase in body weight following hepatocyte-specific p53 ablation was independent of food intake and associated with a decrease in energy expenditure, the mechanism of action underlying this impairment likely relates to p53's role in mitochondrial energetics. 7,8,35 Considering that the increase in body weight following hepatocyte-specific p53 ablation was independent of food intake and associated with a decrease in energy expenditure, the mechanism of action underlying this impairment likely relates to p53's role in mitochondrial energetics.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in whole-body p53 KO mouse models report conflicting findings on the effect of p53 KO on body weight and metabolic homeostasis, with some studies finding that p53 KO decreases body weight and improves glucose regulation in mice on HFD 38 and others finding the opposite. 7,8,10 The discrepancy in findings in whole-body p53 KO models, maybe due to, in part, the development of compensatory pathways. 7,8,10 The discrepancy in findings in whole-body p53 KO models, maybe due to, in part, the development of compensatory pathways.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the PVH action on BAT activity seems 530 more related to a modulatory role, whereas a direct control 531 remains unclear. In this sense, it has been reported that direct stimulations of PVH do not induce effects on BAT activity 533 [174,175], whereas the inhibitory projections from the PVH to the rRPa could be implicated in the decrease of the sympa-535 thetic activity of the BAT [175,176]. tryptophan activate BAT thermogenesis [178,[191][192][193].…”
Section: Central Regulation Of Thermogenesismentioning
confidence: 99%